Obtenção de nanopartículas fluorescentes de quitosana para potencial aplicação biomédica - Padilha, Andreia De Carvalho (2019)
The bioimaging technology allied to nanomedicine is a field of great demand on developing materials that do not require invasive techniques and which present properties that allow their biological application. Chitosan is a biopolymer that presents interesting biomedical applications due to its biocompatibility, biodegradability and low toxicity. In contrast, its low quantum natural yield limits its use in the bioimaging area. In this context, this work focused on the fluorescence study of chitosan nanoparticles obtained by hydrothermal treatment at different temperatures and exposure times using hydrochloric acid, citric acid and acetic acid as solvents. Subsequently, the drug methotrexate (MTX) was incorporated into the Q-HCl nanoparticles. The particles were characterized by Fourier transform infrared spectroscopy (FTIR), particle size distribution by dynamic light scattering (DLS) and surface charge (Zeta potential). In the study of the photoluminescent properties of the chitosan particles, these were characterized by UV-visible spectroscopy, fluorescence spectroscopy and quantum yield. In addition, with the nanoparticles incorporated with MTX the efficiency of incorporation of the drug was evaluated. The synthesis with hydrochloric acid and citric acid were effective in the formation of nanoparticles, as evidenced by DLS analysis. The FTIR spectra demonstrated that the chitosan characteristic structure was maintained and that there was interaction with the acid. UV-visible and fluorescence spectra for chitosan-hydrochloric acid and chitosan-acetic acid showed that the decrease in nanoparticle size is accompanied by a change in the fluorescence intensity of the absorption, excitation and emission bands. The increase in fluorescence intensity was confirmed by the determination of the quantum yield of the particles, evidencing that the hydrothermal treatment potentiates its photoluminescent properties, presenting a 75-fold increase for the chitosan-hydrochloric acid nanoparticles synthesized at the conditions of 150°C for 120 minutes. Through thermal analysis it was observed that the incorporation of MTX provided an improvement in the thermal stability of the nanoparticles. Finally, the morphological analysis by SEM showed a correlation with the mean diameters obtained by DLS, demonstrated the spherical shape of the chitosan-hydrochloric acid and chitosan-citric acid nanoparticles, as well as the increase in size of chitosan nanoparticles after incorporation of MTX. The interaction between drug and chitosan was also observed in the FTIR spectra and the incorporation of MTX to the chitosan-hydrochloric acid nanoparticles was 72.9%, accompanied by changes in the nanoparticle formats.